Credit guarantees and subsidies when lender has a market power - Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2011)
Provision of credit guarantees or subsidies may remove an adverse selection leading to credit rationing. This paper concentrates on comparison of government budget costs of credit guarantees and subsidies in a monopolistic credit market. Different opportunity costs among entrepreneurs, which reflect different mixes of general and human specific capital, generate different outcomes in the model. As long as the participation costs of low-risk entrepreneurs are sufficiently close to the participation costs of high-risk entrepreneurs, the budget-cost minimizing government should prefer guarantees over interest rate subsidies as an intervention instrument.
Keywords: D82; G18; H25; 330; credit; subsidies; guarantees